Lactobacillus acidophilus Attenuates Salmonella-Induced Stress of Epithelial Cells by Modulating Tight-Junction Genes and Cytokine Responses - Lépine, Alexia F. P.; de Wit, Nicole; Oosterink, Els; Wichers, Harry; Mes, Jurriaan; de Vos, Paul (Frontiers in Microbiology, 2018)
Scope: Salmonellosis is a prevalent food-borne illness that causes diarrhea in over 130 million humans yearly and can lead to death. There is an urgent need to find alternatives to antibiotics as many salmonellae are now multidrug resistant. As such, specific beneficial bacteria and dietary fibers can be an alternative as they may prevent Salmonella Typhimurium (STM) infection and spreading by strengthening intestinal barrier function. Methods and results: We tested whether immune active long-chain inulin-type fructans and/or L. acidophilus W37, L. brevis W63 and L. casei W56 can strengthen barrier integrity of intestinal Caco-2 cells in the presence and absence of a STM. Effects of the ingredients on intestinal barrier function were first evaluated by quantifying trans-epithelial electric resistance (TEER) and regulation of gene expression by microarray. Only L. acidophilus had effects on TEER and modulated a group of 26 genes related to tight-junctions. Inulin-type fructans, L. brevis W63 and L. casei W56 regulated other genes, unrelated to tight junctions. L. acidophilus also had unique effects on a group of 6 genes regulating epithelial phenotype towards follicle-associated epithelium. L. acidophilus W37 was therefore selected for a challenge with STM and prevented STM-induced barrier disruption and decreased secretion of IL-8. Conclusion: L. acidophilus W37 increases TEER and can protect against STM induced disruption of gut epithelial cells integrity in vitro. Our results suggest that selection of specific bacterial strains for enforcing barrier function may be a promising strategy to reduce or prevent STM infections.